Parity and anemia among pregnant women at a public health center in Bojonegoro, Indonesia - Siswantoro, Toto; Ernawati, Masfuah (Universitas Airlangga, 2023)
HIGHLIGHTS One of the most common maternal health problems is anemia during pregnancy Factors that lead to anemia incidence were analyzed to be able to provide adequate precautions. It was found that knowledge, parity, and consistency in taking blood supplement tablets during pregnancy are factors that influence the incidence of anemia in pregnant women. ABSTRACT Objective: The purpose of this study was to analyze the factors that influenced anemia in pregnant women at the Public Health Center of Kedewan, Bojonegoro, Indonesia. Materials and Methods: This was an analytic study using a retrospective approach. The population of this study was all pregnant women in 2018 at Public Health Center in Kedewan, Bojonegoro, Indonesia, involving 173 pregnant women, consisting of 117 anemic pregnant women and 56 non-anemic pregnant women. The sample of this study consisted of 119 pregnant women in 2018 consisting of 80 anemic pregnant women and 39 non-anemic pregnant women, who were selected using proportional stratified random sampling and simple random sampling. Bivariate and multivariate analyses were performed using multiple logistic regression. Results: Variables that did not significantly affect anemia in pregnant women were age (p=0.384), education (p=0.460), occupation (p=0.234), income (p=0.482), food abstinence (p= 0.465), and ANC examination (p=0.319), while variables that significantly affected anemia in pregnant women were knowledge (p=0.002), parity (p=0.000) and the regularity of consuming blood-booster tablets (p=0.041). Conclusion: The most influential variable on anemia in pregnant women was parity.